The Image of the Czech Past in the Contemporary Docudrama - Merenus, Aleš; Lollok, Marek (Porównania, 2020)
This study attempts to depict, describe and analyse the intersection of documentary material with the structure and, by extension, the fictional worlds of current drama texts. On the basis of selected examples, it presents several types of Czech docudrama, from biographically-based plays and “tribunal dramas” to stage collages. The common denominator behind these texts is their attempt to create an impression of authenticity among recipients, as well as “faithfulness” to reality. Their main objective is to provide a fresh interpretation of a historical event or to present or rehabilitate particular historical figures and, not least, also to recreate collective memory and the Czech national identity within the framework of the Central European cultural space.